Surgical safety issues relating to the use of diathermy in patients with cochlear implants: The patient's perspective. (January 2014) - Frampton, Steven J; Mitchell, Timothy E
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives The number of cochlear implant recipients throughout the world is set to increase markedly. Surgical diathermy used inappropriately in the head and neck region can be damaging to implant electronics and may irreversibly damage the remaining auditory neural pathways. Safety guidelines have been published but many non-implant surgeons are unaware of their existence. We aimed to examine this issue from the patient's perspective. Methods A questionnaire was supplied to 50 adults and the parents of 50 implanted children registered at the South of England Cochlear Implant Centre. Results Adults Forty-six percent felt that non-implant surgeons would be aware of the diathermy restrictions. Only one patient had undergone subsequent surgery. Eighty-six percent still possess their implant identification (ID) card, and 71% carry it with them. Seventy-seven percent felt that if they required surgery they would show their implant ID card and raise the diathermy issue. Parents Although 76% of parents believed that surgeons would be unaware of the diathermy restrictions, none of the 12% of parents whose children underwent subsequent surgery had highlighted the issue to their surgeon. Eighty-four percent of the parents/children possessed their ID card. While only 8% of parents ensured that their child carried it at all times, a further 12% reported in free text that they carry the card on behalf of their children. Conclusion Diathermy use in cochlear implant recipients is a significant patient safety issue. There is a role for further education of patients and surgeons, for better utilization of the ID card, and for increased clarity on manufacturers' websites.